From Solid State Chemistry to Heterogeneous Catalysis. - Ivanova, Svetlana; Odriozola, José A.; Bobadilla, Luis F. (Newcastle-upon-Tyne : Cambridge Scholars Publisher, 2021)
Heterogeneous catalysis is deeply founded on solid state chemistry, but the relationship between the two often appears to be elusive in many cases. It is generally difficult to relate the allusion of symmetry to the crystal structure and the defect chemistry or acid-base properties to the surface reconstruction and extended defects that in most cases are the basis of physicochemical properties and solids applications. This book provides insights into solid state chemistry in order to widen the vision of heterogeneous catalysis. It covers a broad range of solid state related topics, including s.
Intro -- Table of Contents -- Preface -- Chapter 1 -- Chapter 2 -- Chapter 3 -- Chapter 4 -- Chapter 5 -- Chapter 6 -- Chapter 7 -- Appendix I -- Appendix II -- Appendix III -- Additional problems and questions
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Solid state chemistry; Heterogeneous catalysis; Chimie de l'état solide; Catalyse hétérogène.; Chemistry; Catalysis; Heterogeneous catalysis; Solid state chemistry